Anthropometric findings from birth to adulthood and their relation with karyotpye distribution in Turkish girls with Turner syndrome - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (WILEY, 2016)
To evaluate the anthropometric features of girls with Turner syndrome (TS) at birth and presentation and the effect of karyotype on these parameters. Data were collected from 842 patients with TS from 35 different centers, who were followed-up between 1984 and 2014 and whose diagnosis age ranged from birth to 18 years. Of the 842 patients, 122 girls who received growth hormone, estrogen or oxandrolone were excluded, and 720 girls were included in the study. In this cohort, the frequency of small for gestational age (SGA) birth was 33%. The frequency of SGA birth was 4.2% (2/48) in preterm and 36% (174/483) in term neonates (P<0.001). The mean birth length was 1.3cm shorter and mean birth weight was 0.36kg lower than that of the normal population. The mean age at diagnosis was 10.1 +/- 4.4 years. Mean height, weight and body mass index standard deviation scores at presentation were -3.1 +/- 1.7, -1.4 +/- 1.5, and 0.4 +/- 1.7, respectively. Patients with isochromosome Xq were significantly heavier than those with other karyotype groups (P=0.007). Age at presentation was negatively correlated and mid-parental height was positively correlated with height at presentation. Mid-parental height and age at presentation were the only parameters that were associated with height of children with TS. The frequency of SGA birth was found higher in preterm than term neonates but the mechanism could not be clarified. We found no effect of karyotype on height of girls with TS, whereas weight was greater in 46,X,i(Xq) and 45,X/46,X,i(Xq) karyotype groups. (c) 2016 Wiley Periodicals, Inc.
Keywords: anthropometry; karyotype; turner syndrome; GROWTH-HORMONE TREATMENT; HEAD CIRCUMFERENCE; WEIGHT; HEIGHT; CHILDREN